2018
DOI: 10.1590/0102-672020180001e1382
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Laparoscopic Esophagectomy vs. Transhiatal Open Esophagectomy in Achalasia: A Randomized Study

Abstract: Background:Open and laparoscopic trans-hiatal esophagectomy has been successfully performed in the treatment of megaesophagus. However, there are no randomized studies to differentiate them in their results. Aim:To compare the results of minimally invasive laparoscopic esophagectomy (EMIL) vs. open trans-hiatal esophagectomy (ETHA) in advanced megaesophagus. Method:A total of 30 patients were randomized, 15 of them in each group - EMIL and ETHA. The studied variables were dysphagia score before and after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…The prognosis of this aggressive neoplasm depends mainly on the local invasion extension, hematogenous metastasis, and lymphatic spread 20 . Surgical resection is the primary treatment for localized esophageal carcinoma, and a properly lymphadenectomy is crucial for long-term survival 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of this aggressive neoplasm depends mainly on the local invasion extension, hematogenous metastasis, and lymphatic spread 20 . Surgical resection is the primary treatment for localized esophageal carcinoma, and a properly lymphadenectomy is crucial for long-term survival 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In short-term survival, inconsistency was found in previous studies [ 11 , 20 – 22 ]. MIE was found associated with lower in-hospital mortality in a Japanese Inpatient Database (1.2% vs. 1.7%, P = 0.048) [ 20 ] and from a meta-analysis (OR = 0.668, 95% CI 0.539–0.827, P < 0.05) [ 11 ].…”
Section: Discussionmentioning
confidence: 83%
“…Another gap in the literature is the lack of consistent short-term mortality rate data after MIE. Several studies concluded that MIE had favorable outcomes of in-hospital mortality [ 11 , 20 ] while other studies suggested a non-significant result [ 21 , 22 ]. It is important to investigate the POAF risk and short-term mortality after MIE.…”
Section: Introductionmentioning
confidence: 99%
“…Much has been written concerning the transition from open to laparoscopic transhiatal esophagectomy (THE) with cervical anastomosis. 17 Among the benefits of the minimally invasive approach are shorter hospital length of stay, decreased postoperative complications, and lower intraoperative blood loss, while achieving similar oncologic outcomes. 8,9…”
Section: Introductionmentioning
confidence: 99%